CONCENTRATION AND ACCUMULATION THE NUTRIENT FUNCTION OF PLANT POPULATION CANOLA - Conte e CASTRO, Ana Maria; BOARETTO, Antonio Enedi (Scientia Agraria, 2004)
To determine spacing and plant density effects on the nutrient contents of canola, an experiment was installed at Experimental Farm of São Manuel of the Faculdade de Ciências Agronômicas do Campus de Botucatu - SP, in Red Yellow Latosol soil, where the main plots were spacing (broadcast, 18cm and 36cm rows) and the subplots were density (600, 900 and 1.200 thousand plants.ha-1), with four replications. Plants were sampled at 30, 45, 60, 90 and 130 days after emergence for evaluation in the dry matter production and the nutrient content. The results showed that spacing and density influenced nutrient contents. The maximum accumulation for macronutrients was at 45 days after planting and maximum for Zn, Fe and B occurred at 45 days and for Cu and Mn at 60 days after emergence.